SAT0178 THE EFFICACY AND SAFETY OF ANTI-PNEUMOCOCCAL VACCINATION IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS: SYSTEMATIC REVIEW AND META-ANALYSIS. (June 2019) - Adawi, Mohammad; Bragazzi, Nicola Luigi; Mcgonagle, Dennis; Mahroum, Naim; Damiani, Giovanni; Bridgewood, Charlie; Amital, Howard; Watad, Abdulla
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex, multi-factorial chronic systemic autoimmune disease, characterized by a clinically relevant heterogeneity, affecting women more commonly than men. It has an estimated prevalence of 20 to 150 cases per 100, 000 persons. The immune system dysregulation in SLE patients is associated with a higher risk of infections, including pneumococcal pneumonia. Anti-pneumococcal vaccines represent a valuable and effective preventative tool to mitigate and counteract pneumococcal pneumonia. However, the efficacy and safety of anti-pneumococcal immunization in SLE patients is both controversial and not completely agreed upon. Indeed, several epidemiological studies investigating the anti-pneumococcal vaccine safety and efficacy in patients suffering from SLE have reported short-term immunogenicity with elevated anti-pneumococcal antibody titres but inconsistent long-term findings, with some studies finding poor responses, mainly for long-term immune protection. Objectives: We conducted a systematic review and meta-analysis to better understand the efficacy and safety of pneumococcal vaccination administered to SLE patients. Methods: A comprehensive literature search in accordance with the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" (PRISMA) guidelines was performed. We mined also the gray literature and searched also for unpublished studies, presented at congresses either as oral communications or posters. We were able to identify 18 studies. All studies were designed as longitudinal investigations, 2, in particular, were of high quality, being randomized, double-blind trials. Four studies had control groups. Results: Total sample size included 601 participants. Vaccine immunogenicity in terms of subjects with protective antibody titers ranged from 36% to 97.6%. According to our systematic review and meta-analysis, high erythrocyte sedimentation rate (ESR), older age, earlier SLE onset, high disease activity, and immunosuppressive therapy were found to be statistically significant predictors of poor immunogenicity, although belimumab was found to have no significant impact. With regard to safety, no serious adverse events were found, with up to one third of cases reporting mild/low-grade complaints. Conclusion: Due to the high risk of pneumococcal infection in SLE patients and given the safety and, at least partial, effectiveness, according to our systematic review and meta-analysis, in such patients, preventive strategies mainly by immunization, are required in all age groups and, in those needing immunosuppressive therapy, immunization should be given prior the initiation of the treatment. Disclosure of Interests: Mohammad Adawi: None declared, Nicola Luigi Bragazzi: None declared, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB, Naim Mahroum: None declared, Giovanni Damiani: None declared, Charlie Bridgewood: None declared, Howard Amital Grant/research support from: Pfizer, AbbVie, Janssen, Grant/research support from: Pfizer, AbbVie, Janssen, Consultant for: Pfizer, Merck Sharp & Dohme, Consultant for: Pfizer, Merck Sharp & Dohme, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Abdulla Watad: None declared